2002
DOI: 10.1038/sj.ejcn.1601385
|View full text |Cite
|
Sign up to set email alerts
|

Why healthcare workers give prelacteal feeds

Abstract: Objective: Because prelacteal feeds can adversely affect breastfeeding, UNICEF=WHO discourage their use unless medically indicated. The study was carried out to determine the proportion of healthcare workers who routinely give prelacteal feeds, and their reasons for doing so; further, to determine whether any differences exist between medically and non-medically trained healthcare workers in their administration of prelacteal feeds. Design: Survey. Setting: Primary, secondary and tertiary health facilities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 19 publications
2
54
1
Order By: Relevance
“…This has been reported in previous studies. [10][11][12] The risks associated with unpasteurised non-human milk from animals like cow, goat and sheep whether prelacteal or not have previously been documented. 21 This finding could be an indication of the level of awareness in the community on the risks associated with consumption of unpasteurised milk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been reported in previous studies. [10][11][12] The risks associated with unpasteurised non-human milk from animals like cow, goat and sheep whether prelacteal or not have previously been documented. 21 This finding could be an indication of the level of awareness in the community on the risks associated with consumption of unpasteurised milk.…”
Section: Discussionmentioning
confidence: 99%
“…Such reasons include cleansing and preparing the baby's gastrointestinal tract for digestion, quenching thirst, flushing the bladder, affording mother enough time to rest, 9 insufficient breastmilk, unclean colostrum, prevention of dehydration and hypoglycaemia. 10 The types of feeds given vary, and can include plain water, glucose water, infant formula, 10,11 'ghee' (refined butter), honey, 12 herbs, black tea and dilute cow milk. 13 Other forms of pre-lacteal feeds documented include dates, sugar and salt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, prelacteal liquid is given with a finger or a spoon often while the child is asleep or crying, and there is a danger of aspirating the fluid into the air passages and lungs. Thus, this feeding process reduces the practice of exclusive breast feeding which can be dangerous to the child and may even result in death [2]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…27,33 Studies have shown that it could be due to reason of insufficient milk supply. 34,35 In present study 105 (52.5%) babies were given pre-lacteal feed in the form of a honey 57(54.28%) followed by ghutti 27 (25.71%).…”
Section: Discussionmentioning
confidence: 99%